I want to tell you a story (Palíndromo, 2020)
This essay is part of the artistic research I, you, they, us, which approaches autobiographical narratives about love between women. Through performances and texts, I gather memories, reflecting on my past relationships and proposing a relationship with the viewer/participant/reader. This report presents one of the performances, I want to tell you a story, which is about affective, loving and sexual attractions. By meeting a stranger, the desire is put in question: what attracts in another body? What is a lesbian’s body? What stories does it bring? In the contemporary, the private becomes relevant by giving voice to social minorities. This strategy is used in works that have become art history ́s references. Examples include Tracey Emin’s Everyone I ever slept with 1963-1995 – which formally resembles my work –, Nan Goldin’s The Ballad of Sexual Dependency, Sophie Calle’s Take care of yourself and José Leonilson’s drawing series The dedicated ones. These are diverse productions in which the artists make a fictionalization of their own love life. In the course of my performance, the intimacy proposed addresses a constant erasure of lesbian narratives, suggesting possibilities to perform love as a political force.
Keywords: love; autobiography; performance; artists’ writings; lesbian studies